2013
DOI: 10.1111/evo.12164
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Adjustments in Sperm Production Within and Between Two Island Populations of House Mice

Abstract: Sperm production is physiologically costly. Consequently, males are expected to be prudent in their sperm production, and tailor their expenditure according to prevailing social conditions. Differences in sperm production have been found across island populations of house mice that differ in the level of selection from sperm competition. Here, we determined the extent to which these differences represent phenotypic plasticity and/or population divergence in sperm production. We sourced individuals from two pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 67 publications
7
83
0
Order By: Relevance
“…Previously, we found that males from our high sperm competition population produced more sperm and better quality sperm than did males from the low sperm competition population [32]. Moreover, males reared under a perceived risk of sperm competition produced more aggressive sperm compared with males reared under no risk [32].…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Previously, we found that males from our high sperm competition population produced more sperm and better quality sperm than did males from the low sperm competition population [32]. Moreover, males reared under a perceived risk of sperm competition produced more aggressive sperm compared with males reared under no risk [32].…”
Section: Discussionmentioning
confidence: 51%
“…Previously, we found that males from our high sperm competition population produced more sperm and better quality sperm than did males from the low sperm competition population [32]. Moreover, males reared under a perceived risk of sperm competition produced more aggressive sperm compared with males reared under no risk [32]. Adaptive adjustments in the ejaculate would enhance male fitness in competitive situations [24,29] but are also likely to lead to an increased risk of polyspermic fertilizations [10].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Sperm production and mating both pose non-trivial costs to males (Simmons 2001) and numerous studies have illustrated the interaction between social environment and male sexual behaviour both in insects Wigby et al 2009;Bailey 2011;Billeter et al 2012;Bailey et al 2013;Han and Brooks 2013) and vertebrates (Firman et al 2013; recently reviewed by Kelly and Jennions 2011). While males may employ a variety of strategies in response to sperm competition (including, but not restricted to: changes in sperm number (Wedell et al 2002), ejaculation size (Gage 1991;Garcia-Gonzalez and Gomendio 2004); seminal protein composition (Wigby et al 2009;Perry et al 2013) and sperm morphology (Gage 1994) behavioural changes have the benefit of being ''cheaper'' and may allow for more rapid responses to fluctuations in local environment (Bretman et al 2011).…”
Section: Introductionmentioning
confidence: 99%